2020
DOI: 10.3390/jcm9103246
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Program Plus Amygdala and Insula Retraining (MAIR) for the Treatment of Women with Fibromyalgia: A Pilot Randomized Controlled Trial

Abstract: The lack of highly effective treatments for fibromyalgia (FM) represents a great challenge for public health. The objective of this parallel, pilot randomized controlled trial (RCT) was two-fold: (1) to analyze the clinical effects of mindfulness plus amygdala and insula retraining (MAIR) compared to a structurally equivalent active control group of relaxation therapy (RT) in the treatment of FM; and (2) to evaluate its impact on immune-inflammatory markers and brain-derived neurotrophic factor (BDNF) in serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…The investigation of the mechanisms of fibromyalgia is expected to provide important results in the next years. In fact, as to the neurobiological mechanisms referred in the Introduction, namely the immune-inflammatory connection, recent studies indicated that MBSR has regulatory effects of the immune response since it partially corrected the imbalance in the ration of pro- and anti-inflammatory cytokines, along with Brain-Derived Neurotrophic Factor (BDNF) ( Andres-Rodriguez et al, 2019 ; Sanabria-Mazo et al, 2020 ). As to the “brain hypothesis,” and considering that impaired endogenous pain modulation was detected by imaging studies in fibromyalgia patients ( Staud, 2011 ), an interesting study showed that the regional cerebral blood flow is altered in patients with fibromyalgia subjected to mindfulness interventions ( Medina et al, 2022 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…The investigation of the mechanisms of fibromyalgia is expected to provide important results in the next years. In fact, as to the neurobiological mechanisms referred in the Introduction, namely the immune-inflammatory connection, recent studies indicated that MBSR has regulatory effects of the immune response since it partially corrected the imbalance in the ration of pro- and anti-inflammatory cytokines, along with Brain-Derived Neurotrophic Factor (BDNF) ( Andres-Rodriguez et al, 2019 ; Sanabria-Mazo et al, 2020 ). As to the “brain hypothesis,” and considering that impaired endogenous pain modulation was detected by imaging studies in fibromyalgia patients ( Staud, 2011 ), an interesting study showed that the regional cerebral blood flow is altered in patients with fibromyalgia subjected to mindfulness interventions ( Medina et al, 2022 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Los participantes tuvieron cambios significativos y positivos en los resultados del Cuestionario de Aceptación y Acción II, el cual emplearon para medir la FC (p ≤ 0.001). 27 Asimismo, Greenberg y su equipo de trabajo ofrecieron 14 sesiones de atención plena a 32 adultos (aproximadamente tres horas semanales). Aquellos que llevaron a cabo la intervención tuvieron un mejor desempeño en la prueba de la jarra de agua de Einstellung (p ≤ 0.02).…”
Section: Identificaciónunclassified
“…Although the pathogenesis of FM is unknown, imaging has shown that alterations in central sensitization, involving an imbalance of brain-derived neurotrophic factor (BDNF) and inflammatory biomarkers, appear to be implicated [36,37]. Montero-Marin et al [36] sought to assess the impact of attachment-based compassion therapy (ABCT) on BDNF levels and the levels of inflammatory markers, namely, TNF-α, IL-6, IL-10, and the Creactive protein (CRP).…”
Section: Cognitive Behavioral Therapy (Cbt)mentioning
confidence: 99%